TEACHING INTERNATIONAL RELATIONS EXPERTS ENGLISH DIALOGUE COMMUNICATION - Savchak, I. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
In the article it is noted that Ukraine’s entry into the world community is a clear indication of the urgent need for professionals able to possess not only professional qualities, but also knowledge of a foreign language, therefore foreign language training should become a priority task of higher education. The methodology of training international relations specialists to the English dialogue communication has been characterized. The interaction of competitive, cognitive-communicative, personal and professional-oriented approaches to learning has been analyzed. The basic principles (general-didactic and special) that ensure the effectiveness of the educational process have been defined. All defined principles, focused on the development of professional speech of students, are closely interconnected, each of them complements another, therefore they are also interdependent. The traditional methods of teaching English dialogue communication, such as verbal-informative, visual-heuristic and practical-research, and active learning methods (business games, project methods, case-method, analysis of specific situations) have been singled out. Technique as an integral part of the method has been described. Techniques of mental activity (didactic: comparison, generalization, assessment of activities) and techniques of teaching (methodical: the implementation of didactic tasks according to the model, making up a dialogue at a given beginning, working out of a presentation)have been single out. It has been proved that such forms of educational activities as conferences, presentations, excursions, and conducting classes of real professional activity were effective. Non-traditional forms of training contributed to immersing students into professional activities, help them to enhance their professional interest and allow them to demonstrate the ability to interact. The article states that the basis of the preparation of international relations specialists for the English dialogue communication is the expedient choice of forms and principles of training, the development of an excellent method of conducting classes, the use of balanced, thought-out and effective methods and means of teaching.